2007
DOI: 10.1590/s0100-879x2007000300019
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychological dysfunction related to earlier occupational exposure to mercury vapor

Abstract: We assessed the neuropsychological test performances of 26 patients (mean age = 41.5 ± 6.1 years; mean years of education = 9.8 ± 1.8; 20 males) diagnosed with chronic occupational mercurialism who were former workers at a fluorescent lamp factory. They had been exposed to elemental mercury for an average of 10.2 ± 3.8 years and had been away from this work for 6 ± 4.7 years. Mean urinary mercury concentrations 1 year after cessation of work were 1.8 ± 0.9 µg/g creatinine. Twenty control subjects matched for a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
25
0
9

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 25 publications
2
25
0
9
Order By: Relevance
“…4 This study is in agreement with previous results that have not found significant differences in neuropsychological test scores between chloralkali workers exposed to low Hg concentrations and controls. Nevertheless, in that study, concentration of Hg in blood correlated significantly with poorer performances in …”
supporting
confidence: 93%
See 2 more Smart Citations
“…4 This study is in agreement with previous results that have not found significant differences in neuropsychological test scores between chloralkali workers exposed to low Hg concentrations and controls. Nevertheless, in that study, concentration of Hg in blood correlated significantly with poorer performances in …”
supporting
confidence: 93%
“…N eurological and neuropsychological impairment because of exposure to mercury (Hg) vapor has been demonstrated in different occupationally exposed populations, [1][2][3][4] and its toxic effect on the human visual system has been reported in several studies. [5][6][7][8][9][10] Nevertheless, there is no clear knowledge of the level of exposure at which Hg vapor causes adverse effects.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have shown high occurrence of neurological symptoms such as memory problem, sleep disturbances, concentration difficulties and fatigue among dental clinics personnel 8,9) . Studies have also revealed that chronic exposure to mercury may lead to adverse effects such as salivation, gingivitis, insomnia, excitability, depression and sensory losses [10][11][12][13] .…”
Section: Symptoms Of Intoxication In Dentists Associated With Exposurmentioning
confidence: 99%
“…Eye movements are related to functions such as attention, learning and search; pupil changes are present in judgment, reasoning and decisionmaking; flashing the amount is dependent on the attentional status and conducting high level cognitive tasks such as solution problems and making decisions. In this direction, we have been found alterations in neuropsychological tests for visual memory, visuospatial attention related with performances and scores in visual function tests in mercury vapor occupationally intoxicated patients [205,206].…”
Section: Future Perspectivesmentioning
confidence: 99%